Initiation of DNA replication - Stillman, Bruce (Henry Stewart Talks, 2009)
Cell cycle control of DNA replication, Yeast as a model eukaryote, Control of S-phase entry in yeast, Characterization of origins of DNA replication, Modular structure of S. cerevisiae origins, The budding yeast origin recognition complex (ORC), Structure of the ORC-Cdc6 complex, Evolutionary comparison of ORC AAA+ subunits, Proteins required for formation of the pre-Replication Complex (pre-RC), Cell cycle dependent association of yeast initiation proteins with chromatin, ATP-dependent assembly of a pre-RC, Cell cycle regulation of the pre-RC, The chromosome cycle and establishment of pre-RCs, Dynamic assembly and stability of ORC in human cells, Commitment to S-phase and initiation, Cdc45p is associated with chromatin in a cell cycle-dependent manner, Temporal regulation of DNA replication, Dynamics of pre-RC proteins in human cells differ from pre-RC proteins in yeast, Dynamics of human cell ORC and Cdc6 during the cell division cycle, Orc2 and the cell cycle, Initiation of DNA synthesis: the fork, SV40: a simple replicon, DNA replication-dependent chromatin assembly, Initiation of virus DNA replication, Initiation of DNA synthesis, E1 helicase activity on single stranded DNA, Identification of PCNA as a DNA replication protein, Temporal organization of DNA replication in human cell nuclei, Conserved structure (not sequence) of polymerase clamps, Sequential events at the SV40 DNA replication fork, Proteins at the SV40 DNA replication fork, Proteins at the eukaryotic cell DNA replication fork, Challenges for the future
Archived at 2025/05/28